Detection of EGFR Variants in Plasma: A Multilaboratory Comparison of a Real-Time PCR EGFR Mutation Test in Europe - Keppens, Cleo; Palma, John F; Das, Partha M; Scudder, Sidney; Wen, Wei; Normanno, Nicola; van Krieken, J Han; Sacco, Alessandra; Fenizia, Francesca; Gonzalez de Castro, David; Hönigschnabl, Selma; Kern, Izidor; et al. (The Journal of molecular diagnostics, 2018)
Molecular testing of EGFR is required to predict the response likelihood to targeted therapy in non-small cell lung cancer. Analysis of circulating tumor DNA in plasma may complement limitations of tumor tissue. This study evaluated the interlaboratory performance and reproducibility of a real-time PCR EGFR mutation test (cobas EGFR Mutation Test v2) to detect EGFR variants in plasma. Fourteen laboratories received two identical panels of 27 single-blinded plasma samples. Samples were wild type or spiked with plasmid DNA to contain seven common EGFR variants at six predefined concentrations from 50 to 5000 copies per milliliter. The circulating tumor DNA was extracted by a cell-free circulating DNA sample preparation kit (cobas cfDNA Sample Preparation Kit), followed by duplicate analysis with the real-time PCR EGFR mutation test (Roche Molecular Systems, Pleasanton, CA). Lowest sensitivities were obtained for the c.2156G>C p.(Gly719Ala) and c.2573T>G p.(Leu858Arg) variants for the lowest target copies. For all other variants, sensitivities varied between 96.3% and 100.0%. All specificities were 98.8% to 100.0%. Coefficients of variation indicated good intralaboratory and interlaboratory repeatability and reproducibility but increased for decreasing concentrations. Prediction models revealed a significant correlation for all variants between the predefined copy number and the observed semiquantitative index values, which reflect the samples' plasma mutation load. This study demonstrates an overall robust performance of the real-time PCR EGFR mutation test kit in plasma. Prediction models may be applied to estimate the plasma mutation load for diagnostic or research purposes.
Keywords: Models, Genetic; modely genetické; algoritmy; Circulating Tumor DNA; Real-Time Polymerase Chain Reaction; zkreslení výsledků (epidemiologie); Algorithms; Gene Dosage; Europe; Evropa; Bias; Sensitivity and Specificity; ErbB Receptors; mutace; kvantitativní polymerázová řetězová reakce; Mutation; Humans; cirkulující nádorová DNA; erbB receptory; senzitivita a specificita; genová dávka; lidé